Highly active and novel A-site deficient symmetric electrode material (Sr0.3La0.7)1−x (Fe0.7Ti0.3)0.9Ni0.1O3−δ and its effect on electrochemical performance of SOFCs. (16th February 2021) - Hanif, Muhammad Bilal; Gao, Jiu-Tao; Shaheen, Kausar; Wang, Yue-Peng; Yasir, Muhammad; Li, Chang-Jiu; Li, Cheng-Xin
Abstract: A-site deficient (Sr0.3 La0.7 )1-x (Fe0.7 Ti0.3 )0.9 Ni0.1 O3-δ ((SL)1-x FTN) symmetrical electrodes with compositions x = 0.1, 0.2 and 0.3 denoted as SLFTN-01, SLFTN-02, and SLFTN-03 respectively were synthesized via modified Pechini method. The as prepared samples were further coated on LGSM electrolyte through screen-printing technique. Electrochemical performance was significantly improved for A-site deficient (SL)1-x FTN due to increased concentration of oxygen vacancy. XRD patterns revealed better reversibility for (SL)1-x FTN with rhombohedral structure. Low polarization resistance (Rp) ~0.210, 0.195 and 0.165 Ωcm 2 (in dry H2 ) and 0.069, 0.046 and 0.043 Ωcm 2 (in air) was measured for SLFTN-01, SLFTN-02, and SLFTN-03 respectively at a temperature of 750 °C. Highest conductivities ~326, 338 and 342 Scm −1 were calculated in air and the conductivities obtained in dry H2 were ~0.64, 0.81 and 1.01 Scm −1 at 700 °C. It was observed that small polaron mechanism was responsible for the decreased conductivity with the increased temperature range. The fabricated symmetrical cell ((SL)1-x FTN/LDC|LSGM|LDC/(SL)1-x FTN), maintained good stability without any degradation during the test time ~500 h (in air) and 100 h (in dry H2 ). The detailed investigations categorized the fabricated cells well suited as anode and cathode with improved performance and excellent stability both in oxidizing and reducing atmospheres. Highlights: Symmetrical Solid Oxide Fuel Cells (SOFCs) i.e. (SL)1-x FTN. Improved conductivity and enhanced power density at intermediate temperatures. Better stability for ~100 h in dry H2 and ~500 h in air.